A comparative study: verbal versus printed guiding grid - Letchumanan, Kanthimathi; Devarajoo, Karthiyaini; Muthusamy, Paramasivam (Universiti Putra Malaysia Press, 2014)
Assessment is a crucial part of education as it provides information to be used as feedback to support the teaching and learning process. Oral assessment is conducted at both primary and secondary schools in Malaysia. Previous researches highlight that students are unable to score well in their oral assessment. Therefore, the aim of this study is to examine the effectiveness of sharing assessment criteria, the Guiding Grid (GG), with students to improve oral performance among them. This study was conducted with Form Four students from an urban school. The students' oral assessments were conducted three times and their scores were recorded. The first assessment was done without sharing the GG with the students. Before the second assessment the researchers shared the GG verbally. Finally, 12 students who scored below the satisfactory level were given the printed GG and were assessed for the third time. The findings show a marked improvement in students' oral performance after the sharing of GG, orally as well as in print form. There is a significant improvement on the 12 selected students' oral performance when the printed GG was shared with them. This study also explores students' opinions on sharing the GG with them.